First experience with the new GORE® septal occluder for the closure of multiple atrial septal defects. Issue 7 (27th February 2013) - Freixa, Xavier; Garceau, Patrick; Asgar, Anita W.
<x xml:space="preserve">Abstract</x> Transcatheter closure of an atrial septal defect (ASD) is considered the standard of care for most of the patients with secundum ASD. The existence of multiple or fenestrated ASD may constitute a challenge to achieve a satisfactory result. Data on the usage of multiple devices for closing multiple defects are limited. The GORE® Septal Occluder (GSO) represents a new generation of transcatheter ASD occluders with a design that provides superior conformability, apposition, and closure performance compared with the previous GORE® HELEX device. The present case report describes the first clinical experience with the implantation of two GSO devices in a patient with multiple ASDs and fenestrated septum. © 2012 Wiley Periodicals, Inc.